Surface-modified copper current collector and preparation method and application thereof
Patent Information
- Application Number
- CN202611341303.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-31
- Publication Date
- 2026-10-30
AI Technical Summary
但这类方法存在明显局限性:制备工艺流程复杂、成本较高,难以实现工业化推广;纳米结构的稳定性不足,长期循环后易发生结构坍塌;且部分3D纳米材料(如CuO)导电性较差,会增加电池界面阻抗,影响电荷传输效率
[0021]本发明提供了一种表面修饰铜集流体,包括:铜集流体和在所述铜集流体表面由内到外依次原位修饰的亲锂活性金属层和Li2O复合层;所述亲锂活性金属层的厚度为0.5~1μm;所述亲锂活性金属为锡;所述Li2O复合层包括Li2O基体和分布于所述Li2O基体中的锡锂复合相。本发明提供的表面修饰铜集流体中,亲锂活性金属层作为Li2O复合层和铜集流体的粘合层,相比于Li2O复合层,亲锂活性金属层与铜基体直接接触结合力更强,提高了层间的结合稳定性;通过限定亲锂活性金属层的厚度,避免充放电过程中体积膨胀影响结合稳定性;填充在Li2O基体中的锡锂复合相可以作为亲锂位点,降低锂成核过电位,诱导锂优先在其周围均匀沉积,有助于锂呈颗粒状而非树枝状生长;而且,锡锂复合相在Li2O基体中构建了大量异质界面,能加快Li+的传输;锡锂复合相可以提高Li2O复合层的机械强度,使修饰层在锂沉积-溶出过程保持界面完整性。实施例的结果显示,本发明提供的表面修饰铜集流体组装无负极锂离子电池,10个循环锂沉积颗粒分布均匀,无枝晶;200个循环库仑效率稳定。
Smart Images

Figure CN123017976A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of lithium-ion battery technology, specifically relating to a surface-modified copper current collector, its preparation method, and its application. Background Technology
[0002] With the rapid development of electric vehicles, portable electronic devices, and large-scale grid energy storage, the market demand for lithium-ion batteries (LIBs) has increased significantly. The energy density of LIBs directly affects the range, size, weight, and overall performance of devices.
[0003] To meet the growing market demand, especially the pursuit of longer driving range and lighter battery systems in electric vehicles, improving battery energy density has become a core driving force for technological development. Furthermore, reducing the use of battery materials, lowering system costs, and promoting a cleaner energy structure have further intensified the urgent need for high-energy-density batteries.
[0004] Anode-free lithium metal batteries (AFLMBs) are considered the most promising new type of lithium metal battery for industrial applications due to their high energy density potential, low cost, and manufacturing safety. Unlike traditional LIBs, AFLMBs do not require a graphite anode to accommodate Li. + Li during charging + Directly reducing and depositing lithium metal on copper current collectors, and then stripping it off during discharge, can significantly improve energy density (potential energy density up to 500Wh / kg), and is expected to revolutionize battery energy density levels.
[0005] Despite the advantages of AFLMB, such as high energy density and simple structure, Li + The low reversibility of deposition and dissolution on copper current collectors severely limits their large-scale application. Specifically, this manifests as follows: (1) Copper has no chemical affinity for lithium, while Li... + Uneven deposition on the Cu surface easily leads to dendrite formation, resulting in a decrease in the battery deposition-dissolution coulombic efficiency (CE); (2) lithium dendrites may puncture the separator, causing serious safety hazards; (3) the high specific surface area of dendrites will accelerate electrolyte decomposition, leading to electrode passivation during long-term cycling and ultimately damaging the battery. Therefore, improving the Li + The reversibility and uniformity of deposition-dissolution on copper current collectors are key to the practical application of AFLMB. Moreover, traditional copper foil current collectors often have an oxide layer on their surface, which has poor affinity for lithium and microscopic defects, which can easily lead to uneven current density distribution and further aggravate lithium dendrite growth and volume expansion.
[0006] To address the aforementioned issues, existing research primarily employs three approaches: optimizing and constructing the lithium metal structure; introducing lithiophilic coatings or heterogeneous interface-modified current collectors to lower the nucleation energy barrier; and optimizing the electrolyte interface (SEI) through electrolyte engineering. Since the negative electrode current collector in commercially viable battery systems is still copper foil, which determines the initial deposition morphology of lithium metal, modifying the current collector to improve the interfacial behavior of negative electrode-less lithium metal batteries offers significant technological advantages without requiring replacement of existing production line equipment, demonstrating immense potential for industrial application.
[0007] Modification of current collectors mainly includes two categories. One is the structural design of the current collector itself, such as constructing 3D nanostructured current collectors, utilizing their high specific surface area and porous characteristics to reduce local current density, provide sufficient space for lithium deposition, and induce uniform lithium deposition. The other is the growth of CuO nanostructures on the surface of copper foil through in-situ chemical precipitation, hydrothermal methods, thermal oxidation, etc., or the preparation of 3D porous copper current collectors through chemical gold removal methods and template methods. However, these methods have obvious limitations: the preparation process is complex and costly, making it difficult to achieve industrial-scale promotion; the stability of the nanostructures is insufficient, and structural collapse is prone to occur after long-term cycling; and some 3D nanomaterials (such as CuO) have poor conductivity, which will increase the battery interface impedance and affect charge transport efficiency.
[0008] Another approach involves coating and modifying the copper foil surface, such as coating it with various carbon materials. These materials leverage the excellent conductivity, chemical stability, and porous structure of carbon to improve the compatibility between the current collector and the active material, inhibit electrolyte corrosion of the current collector, and induce uniform lithium deposition. Existing carbon coating materials mainly include graphene, carbon nanotubes, and activated carbon, among which biomass-derived carbon has attracted significant attention due to its wide availability, low cost, and environmental friendliness. However, existing biomass carbon coating technologies still have drawbacks: the pore structure and surface properties of biomass carbon are difficult to control; unactivated or insufficiently activated carbon materials have limited specific surface area, making it difficult to effectively disperse current density; the bonding strength between the carbon coating and the copper foil substrate is insufficient, leading to easy detachment during long-term cycling and a sharp decline in battery performance; and the inherent "lithophobicity" of carbon materials increases the lithium nucleation overpotential, hindering uniform lithium deposition. Other coating materials, including various metal-organic frameworks (MOFs), form a highly lithiophilic interface layer, reducing the lithium deposition nucleation overpotential, guiding uniform lithium ion deposition, and thus inhibiting dendrite growth. However, the poor chemical and thermal stability of MOF materials, as well as the high cost and difficulty in large-scale production, limit the industrial application of this modified coating.
[0009] Inspired by interfacial membrane engineering, a LiF-rich inorganic layer in the interfacial membrane can be more conducive to obtaining dendrite-free lithium metal deposition. However, LiF has low ionic conductivity, limiting the rapid transport of lithium ions, and its high brittleness means that changes in electrode volume can lead to breakage or damage to the SEI film, thus affecting battery life. Lithium oxide (Li₂O) has a lower Young's modulus than LiF, is more resistant to elastic deformation, and has better flexibility, making it more adaptable to volume changes during long-term deposition-dissolution of lithium metal and reducing the risk of breakage. Furthermore, Li₂O has higher lithiophilicity and higher ionic conductivity than LiF, which is beneficial for improving lithium ion transport rates. However, it is worth noting that LiF or Li₂O interfacial films formed through electrolyte engineering are usually discontinuous phases, leading to reduced uniformity of interfacial current density distribution, which in turn can cause dendrite formation and affect the cycle stability of the battery. Summary of the Invention
[0010] The purpose of this invention is to provide a surface-modified copper current collector, its preparation method, and its application. The surface-modified copper current collector provided by this invention exhibits uniform deposition, stable structure, and no dendrite formation during the lithium deposition-dissolution process, resulting in good cycle stability of the assembled battery.
[0011] To achieve the above-mentioned objectives, the present invention provides the following technical solution: The present invention provides a surface-modified copper current collector, comprising: a copper current collector and a lithium-philic active metal layer and a Li2O composite layer sequentially modified in situ from the inside to the outside on the surface of the copper current collector; the thickness of the lithium-philic active metal layer is 0.5~1μm; the lithium-philic active metal is tin; the Li2O composite layer comprises a Li2O matrix and a tin-lithium composite phase distributed in the Li2O matrix.
[0012] Preferably, the thickness of the Li2O composite layer is 2~4μm.
[0013] Preferably, the lithium-loving active metal layer is composed of nanoparticles with an average particle size of 20-50 nm.
[0014] The present invention also provides a method for preparing the surface-modified copper current collector described in the above technical solution, comprising the following steps: A lithium-philic active metal is chemically deposited on the surface of a copper current collector to obtain a copper current collector modified with a lithium-philic active metal. The surface of the lithium-loving active metal layer of the lithium-loving active metal modified copper current collector is subjected to weak oxidation to obtain an oxide-modified copper current collector; the weak oxidation is carried out in an air atmosphere; the temperature of the weak oxidation is 70~110℃ and the time is 10~14h. The oxide-modified copper current collector is subjected to an in-situ electrochemical reaction to obtain a surface-modified copper current collector.
[0015] Preferably, the in-situ electrochemical reaction includes: using the oxide-modified copper current collector as the working electrode and metallic lithium as the counter electrode, and carrying out an electrochemical reduction reaction in an electrochemical cell.
[0016] Preferably, the current density of the in-situ electrochemical reaction is 0.1~1 mA / cm². 2 The in-situ electrochemical reaction takes 1 to 10 hours.
[0017] Preferably, the method for chemically depositing the lithium-loving active metal is electroless plating.
[0018] Preferably, the electroless plating solution is an organic tin salt tin plating solution.
[0019] Preferably, the electroless plating temperature is 60~85℃ and the time is 15~60s.
[0020] The present invention also provides a negative electrode-free lithium-ion battery, comprising a positive electrode, an electrolyte, a separator, and a copper current collector, wherein the copper current collector is the surface-modified copper current collector described in the above technical solution.
[0021] This invention provides a surface-modified copper current collector, comprising: a copper current collector and a lithium-philic active metal layer and a Li2O composite layer sequentially modified in situ from the inside to the outside on the surface of the copper current collector; the thickness of the lithium-philic active metal layer is 0.5~1μm; the lithium-philic active metal is tin; the Li2O composite layer comprises a Li2O matrix and a tin-lithium composite phase distributed in the Li2O matrix. In the surface-modified copper current collector provided by this invention, the lithium-philic active metal layer serves as a bonding layer between the Li2O composite layer and the copper current collector. Compared to the Li2O composite layer, the lithium-philic active metal layer exhibits stronger direct contact bonding with the copper matrix, improving the interlayer bonding stability; by limiting the thickness of the lithium-philic active metal layer, the volume expansion during charging and discharging is avoided from affecting the bonding stability; the tin-lithium composite phase filled in the Li2O matrix can act as lithium-philic sites, reducing the lithium nucleation overpotential and inducing lithium to preferentially and uniformly deposit around it, which helps lithium grow in a granular rather than dendritic manner; moreover, the tin-lithium composite phase constructs a large number of heterogeneous interfaces in the Li2O matrix, which can accelerate the growth of Li... + The transport of lithium is enhanced; the tin-lithium composite phase can improve the mechanical strength of the Li2O composite layer, enabling the modified layer to maintain interfacial integrity during the lithium deposition-dissolution process. The results of the embodiments show that the surface-modified copper current collector assembly of the present invention produces a negative electrode-free lithium-ion battery with uniform lithium deposition particle distribution and no dendrites after 10 cycles; and a stable coulombic efficiency after 200 cycles. Attached Figure Description
[0022] Figure 1 This is a schematic diagram illustrating the preparation of the surface-modified copper current collector in an embodiment of the present invention; Figure 2This is a surface SEM image of the tin-plated copper current collector in Embodiment 1 of the present invention; Figure 3 This is a surface SEM image of the tin-plated copper current collector in Embodiment 3 of the present invention; Figure 4 The XRD patterns are of the oxide-modified copper current collectors in Examples 1-2 and Comparative Examples 1-3 of this invention. Figure 5 This is the XPS image of the oxygen element in the oxidized copper current collector in Example 1 of the present invention; Figure 6 This is the XPS image of tin element in the oxidized copper current collector in Example 1 of the present invention; Figure 7 This is a cross-sectional SEM image of SnO / Sn@Cu in Embodiment 1 of the present invention; Figure 8 This is a cross-sectional elemental distribution diagram of SnO / Sn@Cu in Embodiment 1 of the present invention; Figure 9 This is a cross-sectional elemental composition diagram of SnO / Sn@Cu in Embodiment 1 of the present invention; Figure 10 This is a surface SEM image of SnO / Sn@Cu in Embodiment 1 of the present invention; Figure 11 This is a high-magnification SEM image of the SnO / Sn@Cu surface in Example 1 of the present invention; Figure 12 This is the XRD pattern of the surface-modified copper current collector in Embodiment 1 of the present invention; Figure 13 This is an XPS image of lithium in the surface-modified copper current collector of Embodiment 1 of the present invention; Figure 14 This is a SEM image of the surface-modified copper current collector in Test Example 5 of this invention after 10 charge-discharge cycles; Figure 15 This is a high-magnification SEM image of the surface-modified copper current collector in Test Example 5 of this invention after 10 charge-discharge cycles; Figure 16 This is a SEM image of the unmodified copper foil in Test Example 5 of the present invention after 10 charge-discharge cycles; Figure 17 This is a graph showing the coulombic efficiency curves of lithium metal deposition-dissolution in different negative electrode-free lithium-ion batteries in Test Example 5 of this invention. Figure 18 This is a deposition-dissolution coulombic efficiency curve of lithium metal on a modified layer obtained by a larger particle size tin-plated layer in Test Example 5 of the present invention. Detailed Implementation
[0023] All raw materials used in this invention are not particularly restricted in their source; they can be purchased from the market or prepared using conventional methods known to those skilled in the art.
[0024] There are no particular restrictions on the purity of any of the raw materials used in this invention. However, this invention preferably uses raw materials of analytical grade or conventional purity used in the field of lithium-ion batteries.
[0025] The present invention provides a surface-modified copper current collector, comprising: a copper current collector and a lithium-philic active metal layer and a Li2O composite layer sequentially modified in situ from the inside to the outside on the surface of the copper current collector; the thickness of the lithium-philic active metal layer is 0.5~1μm; the lithium-philic active metal is tin; the Li2O composite layer comprises a Li2O matrix and a tin-lithium composite phase distributed in the Li2O matrix.
[0026] The surface-modified copper current collector provided by this invention includes a copper current collector.
[0027] The present invention does not have any particular limitation on the copper current collector; any copper current collector conventional in the art can be used.
[0028] The surface-modified copper current collector provided by the present invention includes a lithium-philic active metal layer and a Li2O composite layer sequentially modified in situ from the inside to the outside on the surface of the copper current collector.
[0029] In this invention, the lithiophilic active metal is tin. Tin is a lithiophilic metal that can form reversible intermetallic compounds with lithium. During battery charging, it forms intermetallic compounds with lithium to store lithium. During discharge, the intermetallic compounds decompose, releasing lithium again.
[0030] In this invention, the active metal layer is preferably composed of nanoparticles with an average particle size of 20-50 nm. The nanoparticle-based active metal layer ensures structural stability during lithium storage and volume expansion, preventing cracking or pulverization due to volume expansion. Furthermore, it allows for uniform distribution of in-situ formed Li₂O, improving Li₂O efficiency. + Uniformity and stability of transmission.
[0031] In this invention, the thickness of the lithiophilic active metal layer is 0.5~1μm. While ensuring adhesion, the thinner the lithiophilic active metal layer, the more stable the modified layer. The lithiophilic active metal layer acts as an interfacial adhesive layer, firmly bonding the Li2O composite layer to the copper current collector, improving the overall bonding strength of the modified layer. Furthermore, the volume expansion of the lithiophilic active metal during alloying is compressed by the upper Li2O composite layer, enhancing the adhesion between the lithiophilic active metal layer and the copper current collector and reducing interfacial impedance. Within the above-mentioned thickness range, the lithiophilic active metal layer provides sufficient active metal source for the formation of the weak oxide layer while utilizing the residual thin inner lithiophilic active metal layer to improve the adhesion of the Li2O composite layer and enhance the stability of the modified layer.
[0032] In this invention, the Li2O composite layer comprises a Li2O matrix and a tin-lithium composite phase distributed within the Li2O matrix. In the Li2O composite layer, the tin-lithium composite phase can combine with the underlying lithium-affinity active metal to form a gradient of lithium-affinity sites, reducing the lithium nucleation overpotential and "attracting" lithium to deposit uniformly from the inside out in a granular rather than dendritic manner. Furthermore, the tin-lithium composite phase constructs numerous heterogeneous interfaces within the Li2O matrix, accelerating the deposition of lithium. + Transport; the tin-lithium composite phase, as a composite phase, can improve the mechanical strength of the Li2O composite layer and maintain the integrity of the interface.
[0033] In an embodiment of the present invention, the tin-lithium composite phase is Li. x Sn.
[0034] In this invention, the thickness of the Li₂O composite layer is preferably 2~4 μm. Li₂O is Li + Good conductors, which can induce Li + The Li₂O composite layer preferentially deposits uniformly on the surface of the lithium-philic active metal layer and the tin-lithium composite phase; simultaneously, the Li₂O composite layer must withstand the volume expansion during the lithium deposition-dissolution process; the thickness of the Li₂O composite layer within the aforementioned range is beneficial for Li… + Uniform deposition further improves the structural stability of the modified layer.
[0035] In the surface-modified copper current collector provided by this invention, a lithiophilic active metal layer serves as the bonding layer between the Li2O composite layer and the copper current collector. Compared to the Li2O composite layer, the lithiophilic active metal layer exhibits stronger direct contact and bonding with the copper substrate, thus improving the interlayer bonding stability. By limiting the thickness of the lithiophilic active metal layer, the volume expansion during charging and discharging is prevented from affecting the bonding stability. The tin-lithium composite phase filled in the Li2O substrate can act as lithiophilic sites, reducing the lithium nucleation overpotential and inducing lithium to preferentially and uniformly deposit around it, which helps lithium grow in a granular rather than dendritic manner. Moreover, the tin-lithium composite phase constructs a large number of heterogeneous interfaces in the Li2O substrate, which can accelerate the growth of Li. + The tin-lithium composite phase can also serve as a reinforcing phase to improve the mechanical strength of the Li2O composite layer, enabling the modified layer to maintain interface integrity during the lithium deposition-dissolution process.
[0036] The present invention also provides a method for preparing the surface-modified copper current collector described in the above technical solution, comprising the following steps: A lithium-philic active metal is chemically deposited on the surface of a copper current collector to obtain a copper current collector modified with a lithium-philic active metal. The surface of the lithium-loving active metal layer of the lithium-loving active metal modified copper current collector is subjected to weak oxidation to obtain an oxide-modified copper current collector; the weak oxidation is carried out in an air atmosphere; the temperature of the weak oxidation is 70~110℃ and the time is 10~14h. The oxide-modified copper current collector is subjected to an in-situ electrochemical reaction to obtain a surface-modified copper current collector.
[0037] This invention involves chemically depositing a lithium-philic active metal on the surface of a copper current collector to obtain a lithium-philic active metal-modified copper current collector.
[0038] In this invention, the copper current collector is preferably pretreated before chemical deposition, and the pretreatment preferably includes degreasing and activation performed sequentially. Pretreatment can improve the adhesion between the lithium-philic active metal layer and the copper substrate.
[0039] As one embodiment of the present invention, the degreasing can be performed by ultrasonic cleaning with ethanol for 60 seconds; the activation can be performed by immersing the degreased and dried copper current collector in 2 mol / L hydrochloric acid for 10-60 seconds, then washing with water, cleaning with ethanol, and then quickly drying with cold air.
[0040] In this invention, the method for chemically depositing the lithium-philic active metal is preferably electroless plating. Electroless plating is a relatively simple process with low energy consumption, allows for continuous production, and produces a highly uniform metal deposition layer, which facilitates industrial-scale mass production.
[0041] In this invention, the electroless plating temperature is preferably 60~85℃, more preferably 70℃. The temperature of electroless plating affects the deposition rate of the lithiophilic active metal layer and the primary particle size. At lower temperatures, grain growth is dominant, resulting in larger deposited particles. At higher temperatures, nucleation is dominant, leading to the formation of finer, even nanoscale, primary particles. However, excessively high temperatures reduce the stability of the plating solution. Therefore, an electroless plating temperature within the above range is beneficial for quickly obtaining a coating of the desired size and for ensuring uniform deposition of the lithiophilic active metal layer, thus guaranteeing the uniformity of the lithiophilic active metal layer.
[0042] In this invention, the electroless plating time is preferably 15-60 seconds, more preferably 20-25 seconds. The electroless plating time affects the thickness of the coating; a plating time within the above range is beneficial for controlling the deposition thickness of the active metal layer.
[0043] In this invention, the electroless plating solution is preferably an organostannous salt tin plating solution. Organostannous salt tin plating solutions are beneficial for obtaining uniform, nanoscale tin particles. In the embodiments of this invention, the electroless plating solution is a commercially available tin plating solution, the main components of which are: stannous methanesulfonate 12g / L, thiourea 90g / L, sodium hypophosphite 15g / L, hydroquinone 3g / L, methanesulfonic acid 70ml / L, and sodium dodecylbenzenesulfonate 1.5g / ml.
[0044] In one embodiment of the present invention, the electroless plating can be carried out under stirring conditions, wherein the stirring can be magnetic stirring or mechanical stirring.
[0045] As one embodiment of the present invention, the plating layer can be washed with water after chemical plating to remove residual plating solution and then dried with cold air.
[0046] In one embodiment of the present invention, the tin plating thickness in the active metal-modified copper current collector can be 1~2 μm. Some tin will be consumed during the subsequent weak oxidation process; the tin plating thickness within the above range ensures both the tin source amount of the oxide layer and controls the thickness of the underlying tin bonding layer.
[0047] After obtaining the active metal modified copper current collector, the present invention performs weak oxidation on the surface of the active metal layer of the active metal modified copper current collector to obtain an oxide modified copper current collector.
[0048] In this invention, the weak oxidation is carried out in an air atmosphere. The temperature of the weak oxidation is 70~110℃, preferably 80~100℃; as one embodiment of the invention, the temperature of the weak oxidation can be 70℃, 80℃, 90℃, 100℃ or 110℃. The temperature of the weak oxidation affects the degree of oxidation. Within the above temperature range, the active metallic tin can be oxidized to tin suboxide (SnO), which has higher reactivity, avoiding alloying or the formation of stable tin oxide (SnO2), thus providing a reaction basis for subsequent in-situ electrochemical reactions.
[0049] In an embodiment of the present invention, the chemical reaction formula for the weak oxidation is: 2Sn + O2 → 2SnO.
[0050] In this invention, the weak oxidation time is 10-14 hours, preferably 11-12 hours. Within this range, the weak oxidation time allows sufficient lithium-affinity active tin to react to form SnO while the remaining elemental tin in the underlying layer induces the deposition of metallic lithium within the modified layer.
[0051] As one embodiment of the present invention, the weak oxidation can be carried out in a forced-air drying oven or a regular drying oven.
[0052] In one embodiment of the present invention, the thickness of the oxide modification layer in the oxide-modified copper current collector can be 4~8 μm, preferably 5~6 μm. The thickness of the oxide modification layer directly affects the thickness of the final modification layer; a thickness within the above range is beneficial for obtaining a modification layer that meets the requirements.
[0053] In one embodiment of the present invention, the active metal oxide in the oxide-modified copper current collector can be particles with an average particle size of 100~300nm.
[0054] After obtaining the oxide-modified copper current collector, the present invention performs an in-situ electrochemical reaction on the oxide-modified copper current collector to obtain a surface-modified copper current collector.
[0055] In this invention, the in-situ electrochemical reaction preferably includes: using the oxide-modified copper current collector as the working electrode and metallic lithium as the counter electrode, and carrying out an electrochemical reduction reaction in an electrochemical cell. As one embodiment of this invention, the electrochemical cell can be a two-electrode or three-electrode system; as another embodiment, the electrochemical cell can also be assembled using a lithium-ion battery. This invention does not particularly limit the raw materials and assembly method of the electrochemical cell and lithium-ion battery, as long as a normal electrochemical reduction reaction can be carried out. In an embodiment of this invention, the lithium-ion battery is a coin cell.
[0056] In this invention, the current density of the in-situ electrochemical reaction is preferably 0.1~5 mA / cm². 2 More preferably, it is 0.3~1 mA / cm 2 As one embodiment of the present invention, the current density of the in-situ electrochemical reaction can be 0.1 mA / cm². 2 0.2mA / cm 2 0.3mA / cm 2 0.4mA / cm 2 0.5mA / cm 2 0.6mA / cm 2 0.7mA / cm 2 0.8mA / cm 2 0.9mA / cm 2 Or 1mA / cm 2 During the in-situ electrochemical reaction, stannous oxide reacts with Li... + The reaction produces Li₂O and tin, and tin can react with Li + The reaction produces a tin-lithium alloy; the reaction formula is: SnO + 2Li + +2e - →Sn + Li₂O;Sn + xLi + +xe - ⇌Li x Sn; when the current density is within the above range, the reaction of tin oxide can be made uniform and stable, improving the uniformity of Li2O, and further improving the stability of the modified layer and the uniformity of lithium deposition.
[0057] In this invention, the in-situ electrochemical reduction time is preferably 1-10 hours, more preferably 3-6 hours; as one embodiment of this invention, the in-situ electrochemical reduction time can be 1 hour, 2 hours, 3 hours, 4 hours, 5 hours, 6 hours, 7 hours, 8 hours, 9 hours, or 10 hours. A reduction time within the above range is beneficial for the complete reaction of stannous oxide, further improving the stability of the modified layer.
[0058] In an embodiment of the present invention, a schematic diagram of the preparation of the surface-modified copper current collector is shown below. Figure 1 As shown, the process includes: chemically plating activated Cu foil with tin to form a Sn layer on the Cu foil surface; then performing weak oxidation to oxidize part of the Sn in the Sn layer to SnO, forming a SnO-Sn composite layer; and continuing with in-situ electrochemical film formation, where SnO reacts to form Li₂O and Li₂. x Sn, to obtain Li2O matrix and filled Li x Sn dispersed phase, forming Sn layer and Li2O@Li x Heterogeneous modified layer of Sn composite.
[0059] The preparation methods provided by this invention are all industrially mature processes, and the preparation process is easy to control, which is conducive to improving product quality and ensuring performance uniformity; moreover, the process is simple and easy to industrialize.
[0060] The present invention also provides a negative electrode-free lithium-ion battery, comprising a positive electrode, an electrolyte, a separator, and a copper current collector, wherein the copper current collector is the surface-modified copper current collector described in the above technical solution.
[0061] The present invention does not particularly limit the types of the positive electrode, electrolyte and separator; any types conventional in the art can be used.
[0062] As one embodiment of the present invention, the negative electrode-free lithium-ion battery can be a battery with in-situ electrochemical reaction or a reassembled battery.
[0063] The technical solutions of this invention will be clearly and completely described below with reference to the embodiments thereof. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0064] Example 1 A surface-modified copper current collector comprises a copper current collector and a tin layer and a Li2O composite layer sequentially and in situ modified from the inside to the outside on the surface of the copper current collector; the thickness of the tin layer is 0.5~1μm; the tin layer is composed of tin particles with an average particle size of 30nm; the Li2O composite layer consists of a Li2O matrix and Li2O particles distributed in the Li2O matrix. x Composed of Sn nanoparticles; The preparation method is as follows: The copper foil was ultrasonically cleaned with ethanol for 60 seconds to remove the grease on the surface. After cleaning and drying, it was immersed in 2 mol / L hydrochloric acid solution for 15 seconds to activate it. It was then washed with water and ethanol, and quickly dried with cold air to obtain the pretreated copper foil. The pretreated copper foil is immersed in chemical tin plating solution (Tin2000 plating solution provided by Dongguan Shangwei Electronic Materials Co., Ltd.), and tin is plated with magnetic stirring at 70℃ for 20 seconds; then washed with water and dried with cold air to obtain tin-plated copper current collector, with a smooth and bright silver-white tin plating layer; The tin-plated copper current collector obtained above was placed in a forced-air oven and subjected to weak oxidation at 80°C in air atmosphere for 12 hours to obtain an oxide-modified copper current collector (SnO / Sn@Cu). The SnO / Sn@Cu obtained above was cut into 1cm×1cm squares and assembled with lithium metal to form SnO / Sn@Cu||Li coin cells. An electrolyte (DOL / DME-1M LiTFSI-0.2wt% LiNO3) was added, and the electrolyte was set at 1mA / cm². 2 At current density, in-situ electrochemical reduction for 1 hour forms an outer layer of dispersed Li. x A heterogeneous bilayer modified film Li2O@Li with a Sn nanoparticle Li2O composite layer as the inner layer of metallic tin. x Sn / Sn.
[0065] Example 2 A method for preparing a surface-modified copper current collector, the specific steps are the same as in Example 1, except that the temperature of weak oxidation is 110℃.
[0066] Example 3 A method for preparing a surface-modified copper current collector, with the same steps as in Example 1, except that the tin plating solution consists of: 50 g / L stannous chloride, 70 g / L hydrochloric acid, 6 g / L stannous methanesulfonate, 45 g / L thiourea, 7.5 g / L sodium hypophosphite, 1.5 g / L hydroquinone, 35 ml / L methanesulfonic acid, and 0.75 g / ml sodium dodecylbenzenesulfonate; the tin plating temperature is 85°C, and the tin plating time is 60 s.
[0067] Comparative Example 1 A method for preparing a surface-modified copper current collector, the specific steps of which are the same as in Example 1, except that the temperature of weak oxidation is 150℃.
[0068] Comparative Example 2 A method for preparing a surface-modified copper current collector, the specific steps are the same as in Example 1, except that the temperature of weak oxidation is 200℃.
[0069] Comparative Example 3 A method for preparing a surface-modified copper current collector differs from Example 1 in that the weak oxidation is replaced by water vapor-induced catalytic oxidation: after placing the tin-plated copper current collector into a tube furnace, argon gas is introduced for 1 hour to replace the air in the tube furnace, and then the temperature is increased to 80°C at 5°C / min and held for 2 hours; then the temperature is increased to 110°C at 1°C / min, and argon gas that has passed through a water bath is introduced and held for 2.5 hours, and then the temperature is allowed to drop naturally.
[0070] Test Example 1 The tin plating layers in Examples 1 and 3 were observed using a scanning electron microscope, and the SEM images are shown below. Figure 2 , Figure 3 As shown.
[0071] from Figure 2 It can be seen that the tin plating layer in Example 1 is composed of tin particles, which are uniform in size, have a diameter of ~30nm, and have a smooth and fine surface. From Figure 3 It can be seen that the tin particles in the tin plating layer of Example 3 are 0.8~2.5μm in size and have an average particle size of 1.33μm.
[0072] Test Example 2 The oxide-modified copper current collectors in Examples 1-2 and Comparative Examples 1-3 were analyzed using X-ray diffraction, and the XRD patterns are shown below. Figure 4 As shown. Figure 4 In the figures, -110°C represents Comparative Example 3, 200°C represents Comparative Example 2, 150°C represents Comparative Example 1, 110°C represents Example 2, and 80°C represents Example 1.
[0073] Depend on Figure 4 It can be seen that a weak oxidation product, SnO, is generated under dry air. Compared with SnO2, this oxidation product significantly reduces the irreversible active lithium loss during in-situ construction of the Li2O protective layer, and the interface construction is more efficient. Since the Li2O generated by the tin oxide in the subsequent electrochemical reduction is an insulator, the Li2O generated by SnO is thinner than that generated by SnO2, which can effectively reduce the interfacial impedance. As the temperature increases, the diffraction peak representing SnO gradually decreases, while the peak representing the copper-tin alloy gradually increases, indicating that the increase in temperature makes it easier for the solid-phase atomic diffusion of copper and tin to dominate, inducing the formation of copper-rich phase alloys (Cu3Sn or Cu6Sn5), thus inhibiting the oxidation process of tin. This is because the deposited metallic tin primary particles are nanoscale, with extremely high specific surface area and interfacial energy, and the atomic diffusion activation energy is greatly reduced. Solid-phase diffusion will occur below the melting point of metallic tin (231.9℃) to form a copper-tin alloy. Furthermore, in dry air at higher temperatures, oxygen molecules in the air readily react violently on the surface of nano-tin particles, easily leading to uneven oxide layer thickness, which is detrimental to the subsequent formation of a uniform SEI film. Although the water vapor-induced catalytic oxidation method can suppress the formation of alloy phases, the resulting SnO oxide layer exhibits sharper diffraction peaks and narrower full width at half maximum (FWHM), indicating that the SnO obtained by this method has higher crystallinity and larger particle size. Smaller SnO grains are more beneficial to the uniformity of subsequent in-situ electrochemical reduction products.
[0074] The oxide-modified copper current collector in Example 1 was analyzed using X-ray photoelectron spectroscopy, and the XPS image is shown below. Figure 5 , Figure 6 As shown.
[0075] from Figure 5 , Figure 6 It can be seen that the tin in the oxidized copper current collector has both 0 and +2 valences, indicating that SnO was obtained and some Sn was not oxidized.
[0076] Test Example 3 The cross-section of SnO / Sn@Cu in Example 1 was observed using a scanning electron microscope, and the SEM image is shown below. Figure 7 As shown; elemental distribution was measured using an energy dispersive spectroscopy (EDS) instrument, and the resulting elemental distribution map is shown below. Figure 8 As shown, an element proportion diagram was obtained using the accompanying software, as follows. Figure 9 As shown.
[0077] from Figure 7 It can be seen that the SnO / Sn layer has a thickness of 5.8 μm and is dense and uniform; from Figure 8 It can be seen that the surface layer is an oxide layer with a thickness of ~4μm, while the layer close to the copper foil is a metallic tin layer with a thickness of less than 1μm; from Figure 9 It can be seen that the SnO / Sn layer is dominated by tin oxide, with an oxygen mass ratio of 81.93%, indicating that the oxide layer surface also contains a large amount of adsorbed oxygen.
[0078] The surface of SnO / Sn@Cu in Example 1 was observed using a scanning electron microscope, and the SEM image is shown below. Figure 10 , Figure 11 As shown; Figure 11 for Figure 10 A magnified view of the boxed area.
[0079] from Figure 10 , Figure 11 It can be seen that near-spherical primary nanoparticles with a diameter of ~200 nm formed on the surface of SnO / Sn@Cu, and aggregated to form an irregular secondary particle structure. Obvious grain boundary protrusions can be observed between the secondary particles. This secondary structure indicates that oxygen diffusion is slow during the weak oxidation process, and oxidation preferentially occurs at grain boundaries and defects, resulting in localized oxide accumulation. Figure 11 It can be seen that the particles are evenly distributed and relatively uniform in size. This is because the tin particles in the tin plating layer are relatively uniform and small in size, and maintain the characteristics of uniform size and even distribution after oxidation.
[0080] Test Example 4 The surface-modified copper current collector provided in Example 1 was examined using an X-ray diffractometer, and the XRD pattern was obtained, as shown below. Figure 12 As shown.
[0081] from Figure 12It can be seen that the surface-modified copper current collector contains Li. 22 Sn5; no diffraction peaks were observed for Li2O because the Li2O generated by the in-situ electrochemical reaction is amorphous.
[0082] The surface-modified copper current collector provided in Example 1 was analyzed using X-ray photoelectron spectroscopy, and an XPS image was obtained, as shown below. Figure 13 As shown.
[0083] from Figure 13 It can be seen that the surface-modified copper current collector contains Li. x Sn and Li2O.
[0084] Test Example 5 The surface-modified copper current collectors provided in Example 1 and Comparative Example 3 were assembled with metallic lithium to form electrodeless lithium-ion batteries, and deposition-dissolution cycle tests of metallic lithium were conducted at a current density of 1 mA / cm². 2 Deposited charge 1mAh / cm 2 The dissolution voltage was 1.2V. Unmodified copper foil was used as a control.
[0085] After 10 cycles, the morphology of the surface-modified copper current collector provided in Example 1 is as follows: Figure 14 , Figure 15 As shown. The morphology of the unmodified copper foil is as follows. Figure 16 As shown.
[0086] contrast Figure 14 , Figure 15 and Figure 16 It can be seen that the surface-modified copper current collector provided in Example 1 forms uniform lithium particles without dendrites after 10 cycles; while the unmodified copper foil shows significantly uneven lithium deposition after 10 cycles, with local dendrite formation.
[0087] The deposition-dissolution coulombic efficiency graph after 200 cycles is shown below. Figure 17 As shown. From Figure 17 It can be seen that the surface-modified copper current collector provided in Example 1 has a stable coulombic efficiency after 200 cycles, with an average coulombic efficiency of 98.2%. In contrast, the copper foil without surface modification begins to decline rapidly after 50 cycles, and the coulombic efficiency is less than 40% after 100 cycles. Comparative Example 3 shows some improvement compared to the copper foil without surface modification, but the effect is not significant.
[0088] Example 3: The deposition-dissolution coulombic efficiency curve of the assembled battery is shown in Figure 3. Figure 18 As shown. From Figure 18 It can be seen that after the tin deposition particle size is increased to 1.3 μm, although stable cycling is still possible, the average coulombic efficiency decreases to 95.8%.
[0089] As can be seen from the above embodiments and comparative examples, the surface-modified copper current collector provided by the present invention can make lithium deposition uniform, dendrite-free, and structurally stable, thereby improving the cycle stability of negative electrode-free lithium-ion batteries.
[0090] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several improvements and modifications can be made without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A surface-modified copper current collector, comprising: A copper current collector and a lithium-philic active metal layer and a Li2O composite layer sequentially modified in situ from the inside to the outside on the surface of the copper current collector; the thickness of the lithium-philic active metal layer is 0.5~1μm; The lithiophilic active metal is tin; the Li2O composite layer includes a Li2O matrix and a tin-lithium composite phase distributed in the Li2O matrix.
2. The surface-modified copper current collector according to claim 1, characterized in that, The thickness of the Li2O composite layer is 2~4μm.
3. The surface-modified copper current collector according to claim 1, characterized in that, The lithiophilic active metal layer is composed of nanoparticles with an average particle size of 20-50 nm.
4. The method for preparing the surface-modified copper current collector according to any one of claims 1 to 3, characterized in that, Includes the following steps: A lithium-philic active metal is chemically deposited on the surface of a copper current collector to obtain a copper current collector modified with a lithium-philic active metal. The surface of the lithium-loving active metal layer of the lithium-loving active metal modified copper current collector is subjected to weak oxidation to obtain an oxide-modified copper current collector; the weak oxidation is carried out in an air atmosphere; the temperature of the weak oxidation is 70~110℃ and the time is 10~14h. The oxide-modified copper current collector is subjected to an in-situ electrochemical reaction to obtain a surface-modified copper current collector.
5. The preparation method according to claim 4, characterized in that, The in-situ electrochemical reaction includes: using the oxide-modified copper current collector as the working electrode and metallic lithium as the counter electrode, and carrying out an electrochemical reduction reaction in an electrochemical cell.
6. The preparation method according to claim 5, characterized in that, The current density of the in-situ electrochemical reaction is 0.1~1 mA / cm². 2 The in-situ electrochemical reaction takes 1 to 10 hours.
7. The preparation method according to claim 4, characterized in that, The method for chemically depositing lithium-philic active metals is chemical plating.
8. The preparation method according to claim 7, characterized in that, The electroless plating solution is an organic stannous salt tin plating solution.
9. The preparation method according to claim 8, characterized in that, The electroless plating temperature is 60~85℃ and the time is 15~60s.
10. A negative electrode-free lithium-ion battery, comprising a positive electrode, an electrolyte, a separator, and a copper current collector, characterized in that, The copper current collector is the surface-modified copper current collector according to any one of claims 1 to 3 or the surface-modified copper current collector prepared by the preparation method according to any one of claims 4 to 9.